2006
DOI: 10.1016/j.freeradbiomed.2005.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to asbestos-induced lung injury in mice lacking extracellular superoxide dismutase

Abstract: Asbestosis is a chronic form of interstitial lung disease characterized by inflammation and fibrosis that results from the inhalation of asbestos fibers. Although the pathogenesis of asbestosis is poorly understood, reactive oxygen species may mediate the progression of this disease. The antioxidant enzyme extracellular superoxide dismutase (EC-SOD) can protect the lung against a variety of insults; however, its role in asbestosis is unknown. To determine if EC-SOD plays a direct role in protecting the lung fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
67
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 43 publications
9
67
0
Order By: Relevance
“…Lung inflammation was significantly decreased by SOD3 overexpression in mice exposed to CS and elastase. This is in agreement with previous studies showing a protective effect of SOD3 on lung inflammatory responses to hyperoxia, bleomycin, and asbestos (4,17,29,30). Furthermore, the SOD mimetic exhibited a protective effect in lung inflammation in SOD3 KO as well as in WT mice.…”
Section: Discussionsupporting
confidence: 92%
“…Lung inflammation was significantly decreased by SOD3 overexpression in mice exposed to CS and elastase. This is in agreement with previous studies showing a protective effect of SOD3 on lung inflammatory responses to hyperoxia, bleomycin, and asbestos (4,17,29,30). Furthermore, the SOD mimetic exhibited a protective effect in lung inflammation in SOD3 KO as well as in WT mice.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those of previous studies that demonstrated that EC-SOD expression in the lung inhibits inflammation in response to a wide variety of pulmonary injuries. [11][12][13]19 …”
Section: Ec-sod Limits Inflammation After E Coli Inoculationmentioning
confidence: 99%
“…7 This isozyme of the superoxide dismutase family is highly expressed in the lung and arteries and is bound to the extracellular matrix via its positively charged heparin/matrix-binding domain. [7][8][9][10] EC-SOD acts as both an anti-inflammatory and antifibrotic agent in a number of pulmonary diseases including bleomycin-and asbestos-induced pulmonary fibrosis, [11][12][13][14] hyperoxia, [15][16][17] lipopolysaccharide-induced inflammation, 18 and pulmonary infection. 19,20 One mechanism by which EC-SOD inhibits inflammation is directly binding to and inhibiting oxidative fragmentation of several components in the extracellular matrix including collagen, heparan sulfate, and hyaluronan after interstitial lung injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because apoptosis alone does not elicit autoimmunity, a second pro-inflammatory signal such as an adjuvant must be provided in order to generate an immune response (Bondanza et al 2004;Mevorach et al 1998;Tzeng et al 2006). Asbestos induces a highly inflammatory state in the lung (Fattman et al 2006;Kamp and Weitzman 1999;Tan et al 2004). Moreover, exposure to amphibole asbestos in alveolar macrophages has been previously shown to increase the release of proinflammatory cytokines such as TNF-α and IL-1 (Driscoll et al 1995).…”
Section: Discussionmentioning
confidence: 99%